Common property, the Golden Age, and Empire in Acts 2:42-47 and 4:32-35 - Noble, Joshua (London [England] T&T Clark, 2020)
Preface Acknowledgments Abbreviations -- 1. Introduction -- 2. The Golden Age Myth in Greek and Latin Sources -- 3. The Golden Age Myth in Jewish and Christian Sources -- 4. Preliminaries to a Golden Age Reading of the Acts Summaries -- 5. Reading Acts -- 2.42-47 and -- 4.32-35 as Golden Age Allusions -- 6. Conclusion -- Bibliography -- Index
"Joshua Noble focuses on the rapid appearance and disappearance in Acts 2 and 4 of the motif that early believers hold all their property in common, and argues that these descriptions function as allusions to the Golden Age myth. Noble suggests Luke's claims that the believers "had all things in common" and that "no one claimed private ownership of any possessions" - a motif that does not appear in any biblical source - rather calls to mind Greek and Roman traditions that the earliest humans lived in utopian conditions, when "no one ... possessed any private property, but all things were common.""--
Includes bibliographical references and index
Also published in print.
Mode of access: World Wide Web.
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Right of property -- Biblical teaching; Personal belongings; Commons; Biblical studies & exegesis; Electronic books; Hochschulschrift